Study at the Bolted Joint Assembly with Slotted Hole - Ramadhan Prasetya Utama; Alain Daidié (IPTEK Journal of Proceedings Series, 2014)
The bolt as an element which integrates several small parts to a united big structure had been used since a long time ago. This type of impermanent joint holds many advantages in the engineering field such as facilitating the maintenance, particularly at the change of defected part, and also making the delivery of many parts composing a huge structure more sensible by transporting them in diverse modes of transport. One of problems using this type of joint is sometimes it is difficult to assure holes position between parts to be aligned just as designed, in order to facilitate positioning of parts during assembly we could possibly use parts with slotted hole. However, a slotted hole will result in a reduced contact surface between the bolt and parts assembled, therefore the behavior of this type will be clearly different compared to the assembly with normal hole. The research will be conducted with assistance of a finite elements software ABAQUS® for simulating the model along with its parameters and mathematical software Matlab® for interpolating data obtained from the simulation. Firstly, the model will be validated by comparing it to experimental result of research conducted by Bakhiet[1], then its boundary conditions and mesh will be used to next model simulations. Secondly, the parameters of the assembly will be varied such as bolt positions on the part and the modulus Young ratio of bolt and parts. Finally, both assemblies are to be compared (e.g. with normal and slotted hole) and then the assembly’s critical value is to be found by using dimensionless parameters developed by Turgeon and Vadean[2]. From research conducted, we could conclude that the behavior of the assembly, particularly at its fatigue stress produced at the bolt, changes significantly with the variation of the bolt position and also the modulus Young ratio of the bolt and part. A reduced value of fatigue stress produced will be achieved while the bolt position is the nearest possible with respect to the point where load applied. Whereas, a higher modulus Young ratio will convict a higher fatigue stress produced at the bolt